The Development of Social Capital through a Leadership Training Program - Lennox Terrion, Jenepher (Université d'Ottawa | University of Ottawa, 2006)
The objective of this study was to examine how a leadership training program provides a forum for social capital creation through the establishment and maintenance of networks and through discussion and problem solving by participants. This article provides insights into the role of informal learning in management development and shows the critical role of formal training in establishing bonding, bridging and linking social capital.